Development of Interactive Multimedia-Based Project Based Learning (PjBL) Learning Model in PKn Learning in Elementary Schools - Susanti Susanti; Hendri Marhadi; Riandi Marisa (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
The application of the interactive multimedia-based project-based learning (PjBL) learning model in PKn learning in elementary schools is a strategic step to improve the quality of student learning experience. Interactive multimedia is expected to be able to make it easier for students to learn the learning materials they experience. The objectives of this study: 1. To determine the effectiveness of the interactive multimedia-based project based learning (PjBL) model in elementary school learning in Banyuasin III district; 2. To find out the practicality of developing an interactive multimedia-based project based learning (PjBL) model in elementary school learning in Banyuasin III sub-district; 3. Determine the validity of the development of an interactive multimedia-based project based learning (PjBL) model in elementary school learning in Banyuasin III district. The sample used was 175 respondents. Data analysis was carried out using qualitative and quantitative research and for data analysis using descriptive analysis with the help of SPSS 25 for windows. The results of this study show that: 1 The development of an interactive multimedia-based project based learning (PjBL) model received a very valid assessment by validators and media experts; 2 This development product received a practical assessment both theoretically and practically by the validator team which showed the category of 'very practical; 3 The product of the development of a project-based learning model (PjBL) based on interactive multimedia was also declared effective with the increase showing a moderate improvement category.